The study of bioavailability and endogenous circadian rhythm of menaquinone-7, a form of vitamin K 2, in healthy subjects - Du, Fan; Yan, Min; Duan, Lili; Xie, Guolong; Yao, Xiuhua; Hu, Wenjing; Liu, Yu; Meng, Min; Chen, Jiepeng; Shao, Di (British journal of nutrition, 2023)
Menaquinone-7 (MK-7), a multipotent vitamin K 2 , possesses a wide range of biological activities, a precise curative effect and excellent safety. A simple and rapid LC-APCI-MS/MS method for the determination of MK-7 in human plasma with single liquid–liquid extraction (LLE) extraction and 4·5-min analysis time has been developed and validated. Four per cent bovine serum albumin (BSA) was used as surrogate matrix for standard curves and endogenous baseline subtraction. This method was reproducible and reliable and was used to analyse of MK-7 in human plasma. The endogenous circadian rhythm and bioavailability of MK-7 were investigated in two randomised single-dose, open, one-way clinical trials (Study I and Study II). A total of five healthy male subjects were enrolled in Study I and 12 healthy male subjects in Study II. Single-dose (1 mg) of MK-7 was given to each subject under fasting condition, and all eligible subjects were given a restricting VK 2 diet for 4 d prior to drug administration and during the trial. The experiment results of Study I demonstrated that endogenous MK-7 has no circadian rhythm in individuals. Both studies showed MK-7 are absorbed with peak plasma concentrations at about 6 h after intake and has a very long half-life time.